2017
DOI: 10.4172/2155-9597.1000310
|View full text |Cite
|
Sign up to set email alerts
|

Substituted Pyrazolo[3,4-B]Pyridin-3-Ones and Pyrazolo[3,4-B]Pyridine-5- Carbaldehyde, New One-Pot Synthesis Strategy Amelioration Using Vinamidinium Salts, Antibacterial and Antifungal Activities Promising Environmental Protection

Abstract: This review summarizes the current knowledge about the syntheses and biological behavior of some pyrazolo [5,4-b]pyridines. So, an expedient method for the synthesis of 2-phenyl-5-aryl-1,6-dihydropyrazolo [3,4-b]pyridin-3-ones and 2-phenyl-3-oxo-1,6-dihydropyrazolo[3,4-b]pyridine-5-carbaldehyde in a single-step via condensation of vinamidinium salts with 3-amino-1-phenyl-2-pyrazolin-5-one is described according to our recent study with synthesis strategy amelioration. Five derivatives (PYR 1-5 ) were prepared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Pyrazolo-pyridine derivatives have been shown to be antimalarial, antiviral, anti-leishmanial, anti-tubercular, anti-leukemic, antifungal, anxiolytic, osteogenic and have, antitumor activity. Moreover, they have also been studied in management of drug and alcohol addiction, Alzheimer’s disease, infertility and gastrointestinal diseases 14 . Mohamed et al 15 synthesized pyrazolo-cyanopyridine derivatives having antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazolo-pyridine derivatives have been shown to be antimalarial, antiviral, anti-leishmanial, anti-tubercular, anti-leukemic, antifungal, anxiolytic, osteogenic and have, antitumor activity. Moreover, they have also been studied in management of drug and alcohol addiction, Alzheimer’s disease, infertility and gastrointestinal diseases 14 . Mohamed et al 15 synthesized pyrazolo-cyanopyridine derivatives having antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, other bioactive N-containing heterocyclic compounds have been synthesized with a well-known pyrazolopyridine scaffold [20][21][22] and they have numerous pharmacological activities, like, antivirus, antifungal, antimicrobial, antibacterial, antitumor, cancer cell growth inhabitation activities, protein kinase inhibitors, anti-Leishmania, PDE4B inhibitors, B-Raf V600E3 inhibitors, dopaminergic properties, HIF 1-α-prolyl hydroxylase inhibitors. [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] On the other hand, tetrahydrodipyrazolopyridines are also another interesting class of fused heterocycles because of their wide range of biological activities. [39][40][41][42][43][44] In this connection, in the literature, several authors reported many pyrazolopyridine derivatives by innovative methods.…”
Section: Introductionmentioning
confidence: 99%
“…Pyrazolopyridines represent a well‐known scaffold in various bioactive compounds and have numerous pharmacological properties. These compounds exhibit important biological properties, including antibacterial, antimicrobial, antifungal, antitumor, anti‐virus, anti‐Leishmania, HIF 1‐αprolyl hydroxylase inhibitors, B‐Raf V600E3 inhibitors, protein kinase inhibitors, PDE4B inhibitors, dopaminergic properties and cancer cell growth inhabitation activities . The main problems for the synthesis of pyrazolopyridine compounds are long reaction times, utilize of non‐reusable and toxic catalyst and use of particular conditions.…”
Section: Introductionmentioning
confidence: 99%